Atypical Manifestations of Cutaneous Leishmaniasis in a Region Endemic for Leishmania braziliensis: Clinical, Immunological and Parasitological Aspects - Guimarães, Luiz Henrique Santos (2016)
U.S. National Institutes of Health (NIH), through grants NIH P50-AI30639-16 and NIH R03A167663-01. LHG was the recipient of a CAPES.